Indocyanine green nanoparticles useful for photomedicine - Gomes, Anderson J.; Lunardi, Laurelucia O.; Marchetti, Juliana M.; Lunardi, Claure N.; Tedesco, Antonio C. (Mary Ann Liebert, Inc., 2006)
Objective: the aim of this study was to evaluate the potential application of biodegradable nanoparticles (NPs) containing indocyanine green (ICG) in photodynamic therapy (PDT). Methods: Important parameters, such as particle size and external morphology, were established by dynamic light scattering (DLS) and scanning electron microscopy (SEM). Also, drug encapsulation efficiency and in vitro release behavior were evaluated by spectroscopic methods. Results: the particles are spherical in shape, they exhibit an 817-nm diameter, and they have a low tendency to aggregate. The loading efficiency was 65%. ICG photophysical parameters showed a bathocromic shift in ICG-loaded nanoparticles (ICG-NP). Analysis of the cell P388-D1 in the presence of the ICG-NP by SEM showed that the majority of the nanoparticles were uptaken by phagocytic cells after 2 h of incubation. After laser irradiation photodamage was observed in P388-D1 cells where ICG-NPs had been uptaken by phagocytic cells. Conclusion: Polymeric NPs work as an efficient drug delivery system for PDT drugs, and this approach can be used in the administration of amphiphilic photosensitizers in the treatment of neoplasic cells.